An extended conjugate duality for generalized semi-infinite programming problems via a convex decomposition. (2nd August 2020) - Aboussoror, A.; Adly, S.; Salim, S.
ABSTRACT: We present an extended conjugate duality for a generalized semi-infinite programming problem ( P ) . The extended duality is defined in the context of the absence of convexity of problem ( P ), by means of a decomposition into a family of convex subproblems and a conjugate dualization of the subproblems. Under appropriate assumptions, we establish strong extended duality and provide necessary and sufficient optimality conditions for problem ( P ) . These extended conjugate duality and optimality conditions are new in the literature of generalized semi-infinite programming.